A Q-Learning based approach for voltage control in unbalanced distribution system - ÇAKIR, MUSTAFA; CEYLAN, OĞUZHAN (My University, 2023)
In recent years, with the increasing use of renewable energy sources, voltage regulation in power distribution systems has become a greater challenge due to these sources\" intermittent and variable nature. To address this problem, this paper proposes a Q-learning-based method for voltage regulation in power distribution systems that incorporates tap changer voltage regulators when renewable energy sources are present. The voltage deviation problem is formulated as an optimization problem, and Q-learning is used to find near-optimal solutions that can effectively control voltage deviations and improve the overall performance of the power distribution system. The proposed method is applied to power distribution system using OpenDSS incorporated into Python. The simulations are performed on base case IEEE-123 Bus distribution network and with modifications by adding Photovoltaics. From the simulation results we observed that the proposed algorithm is able to solve the overvoltage and undervoltage problems.
Keywords: Tarımsal Bilimler; Ziraat; Tarım Makineleri; Tarımda Enerji; Biyoyakıt Teknolojisi; Bilgi Sistemleri, Haberleşme ve Kontrol Mühendisliği; Sinyal İşleme; Bilgisayar Bilimleri; Algoritmalar; Matematik; Temel Bilimler; Mühendislik ve Teknoloji; Agricultural Sciences; Agriculture; Farm Machinery; Energy in Agriculture; Biofuels Technology; Information Systems, Communication and Control Engineering; Signal Processing; Computer Sciences; algorithms; Mathematics; Computer Science; Natural Sciences; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Temel Bilimler (SCI); Bilgisayar Bilimi; Mühendislik; BİLGİSAYAR BİLİMİ, YAPAY ZEKA; MÜHENDİSLİK, ELEKTRİK VE ELEKTRONİK; ENERJİ VE YAKITLAR; MATEMATİK, UYGULAMALI; MÜHENDİSLİK, İMALAT; Engineering, Computing & Technology (ENG); Natural Sciences (SCI); COMPUTER SCIENCE; ENGINEERING; MATHEMATICS; COMPUTER SCIENCE, ARTIFICIAL INTELLIGENCE; ENGINEERING, ELECTRICAL & ELECTRONIC; ENERGY & FUELS; MATHEMATICS, APPLIED; ENGINEERING, MANUFACTURING; Yapay Zeka; Fizik Bilimleri; Bilgisayar Bilimi Uygulamaları; Enerji Mühendisliği ve Güç Teknolojisi; Yenilenebilir Enerji, Sürdürülebilirlik ve Çevre; Elektrik ve Elektronik Mühendisliği; Emniyet, Risk, Güvenilirlik ve Kalite; Modelleme ve Simülasyon; Artificial Intelligence; Physical Sciences; Computer Science Applications; Energy Engineering and Power Technology; Renewable Energy, Sustainability and the Environment; Electrical and Electronic Engineering; Safety, Risk, Reliability and Quality; Modeling and Simulation; Q-learning; tap changer voltage regulator; unbalanced distribution system